Cyclooxygenase-2 Inhibition Limits Angiotensin II-Induced DNA Oxidation and Protein Nitration in Humans - Pialoux, Vincent; Poulin, Marc J.; Hemmelgarn, Brenda R.; Muruve, Daniel A.; Chirico, Erica N.; Faes, Camille; Sola, Darlene Y.; Ahmed, Sofia B. (Frontiers in Physiology, 2017)
Compared to other cyclooxygenase-2 inhibitors, celecoxib is associated with a lower cardiovascular risk, though the mechanism remains unclear. Angiotensin II is an important mediator of oxidative stress in the pathophysiology of vascular disease. Cyclooxygenase-2 may modify the effects of angiotensin II though this has never been studied in humans. The purpose of the study was to test the effects of selective cyclooxygenase-2 inhibition on plasma measures of oxidative stress, the vasoconstrictor endothelin-1 and nitric oxide metabolites, both at baseline and in respose to Angiotensin II challenge in healthy humans. Measures of 8-hydroxydeoxyguanosine, advanced oxidation protein products, nitrotyrosine, endothelin-1 and nitric oxide metabolites were assessed from plasma samples drawn at baseline and in response to graded angiotensin II infusion (3ng/kg/minx30min, 6ng/kg/minx30 min) before and after 14 days of cyclooxygenase-2 inhibition in 14 healthy subjects (8 male, 6 female) in high salt balance, a state of maximal renin angiotensin system suppression. Angiotensin II infusion increased plasma oxidative stress compared to baseline (8-hydroxydeoxyguanosine; +17%; advanced oxidation protein products; +16%), nitrotyrosine (+76%). Furthermore, levels of endothelin-1 levels were increased (+115%) and nitric oxide metabolites were decreased (-20%). Cycloxygenase-2 inhibition significantly limited the increase in 8-hydroxydeoxyguanosine, nitrotyrosine and the decrease in nitric oxide metabolites induced by angiotensin II infusion, though no changes in advanced oxidation protein products and endothelin-1 concentrations were observed. Cyclooxygenase-2 inhibition with celecoxib partially limited the angiotensin II-mediated increases in markers of oxidative stress in humans, offering a potential physiological pathway for the improved cardiovascular risk profile of this drug.